Successful treatment for patients with von Willebrand disease undergoing urgent surgery using factor VIII/VWF concentrate (Humate-P®) - Thompson, A. R.; Gill, J. C.; Ewenstein, B. M.; Mueller-Velten, G.; Schwartz, B. A. (Haemophilia : the official journal of the World Federation of Hemophilia, 2004)
von Willebrand disease (VWD) is characterized by insufficient von Willebrand factor (VWF) activity. It has been proposed that VWF:ristocetin cofactor (VWF:RCo) activity may be useful in evaluating the response to VWD treatment in patients who require replacement therapy. This prospective, open‐label, non‐randomized study evaluated the safety and efficacy of a factor VIII (FVIII)/VWF concentrate (Humate‐P®) used in treatment regimens based on VWF:RCo activity in subjects with VWD in situations requiring urgent and necessary surgery. This article summarizes the results for 39 subjects with 42 evaluable surgical treatment events, 100% of which were rated as excellent/good for overall efficacy (achievement of haemostasis). The median loading dose based upon VWF:RCo activity was 82.3 international units/kilogram (IU kg−1; range 32.5–216.8 IU kg−1), and the median maintenance dose per infusion was 52.8 IU kg−1 (range 24.2–196.5 IU kg−1) for a median of 3 days (range 1–50 days). The median number of infusions per event was 6 (range 1–67 infusions). Three unanticipated adverse events (peripheral oedema, extremity pain and pseudo‐thrombocytopenia) from two surgical treatment events were reported that were potentially treatment‐related. No serious drug‐related adverse events (AEs) were observed, and no thrombotic events were reported in this study. This study supports the safety and efficacy of the FVIII/VWF concentrate Humate‐P® for the prevention of surgical haemorrhage in patients with VWD when administered in doses calculated in VWF:RCo units.